Hearing loss and dementia: an exploratory study of the views of audiologists. (8th December 2014) - Wright, Nicola; Stickley, Theodore; Mulla, Imran; Bradshaw, Edward; Buckley, Laura; Archbold, Sue
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore audiologists, views and experiences of working with older adults with dementia. Design/methodology/approach – An online survey was distributed to audiologists working in the UK NHS and private sector via their professional organisations. A total of 312 audiologists took part in the study. The survey collected both quantitative and qualitative data. Basic descriptive statistics summarised the quantitative responses. The qualitative data were analysed using conventional thematic approaches. Findings – The quantitative data demonstrated that the vast majority of audiologists had treated someone with dementia (96 per cent). Despite this, 65 per cent of respondents did not feel adequately supported to help this service user population. Four overarching themes were used to explain the qualitative data: integrated and individualised care; formal (including training) vs experiential knowledge; the interaction between dementia and hearing and using the technology. Research limitations/implications – The self-selecting nature of the sample is a limitation which needs to be taken into account when considering the transferability and implications of the findings. Practical implications – Given the anticipated increase in rates of dementia within the population and the potential for hearing impairment to exacerbate the symptoms; this study highlights the unique role audiologists have. The need for more training and development for this professional group is also identified. Originality/value – This is one of the first papers to explore audiologists, views and experiences of working with people with dementia. As such, it highlights some interesting areas worthy of further research using both quantitative and qualitative methods.